Interfaith Harmony in Tajuk, Getasan, Semarang - Ruwandi; Mashlihatul Umami (Jurnal Studi Agama, 2024)
This research aims to explore the narrative of religious harmony values through an ethnographic study of Eid al-Fitr, Christmas and Vesak celebrations in the community of Tajuk, Getasan, Semarang Regency. The importance of this research lies in the effort to understand how interfaith harmony can be maintained and strengthened through religious traditions and celebrations, which in turn can contribute to social stability and harmony in a multicultural society.The research method used is a qualitative approach with data collection techniques through participatory observation, in-depth interviews, and document analysis. The research involved the active participation of various religious believers in Tajuk, who provided in-depth perspectives on the practices and values underlying their religious celebrations.The purpose of this research is to identify and analyze the values of harmony that emerge in the celebrations of Hari Raya Idul Fitri, Hari Raya Natal, and Hari Raya Vaisak, as well as to understand how these values are translated in everyday social interactions. The research also aims to provide practical recommendations for policy makers and community leaders in promoting interfaith harmony. preliminary results show that religious celebrations in Tajuk are not only a spiritual moment but also an occasion to strengthen social ties and interfaith harmony.